Allocation of children's time endowment between schooling and work in rural Ethiopia - Assefa Admassie (University of Bonn, Center for Development Research (ZEF), 2002)
Children have always been part of the economic life of societies. Historical evidence indicates that the contribution of children to family income in cash or in kind has been consistently significant. Currently, the issue of child labor has become an important global development issue in academic research. Empirical evidence indicates that child laborers are found mostly in developing countries and are employed mainly in agriculture and related activities. The aim of this study was to examine the decision-making behavior of subsistence rural households with respect to allocating their children's unit-time endowment among competing activities, including work and school attendance. A multinomial logit model has been used to identify the social, economic and cultural factors influencing household's decision about the allocation of children's time using data from a survey of rural households in Ethiopia. The results show that there are a number of child- and household-specific attributes, culture-and location-specific factors as well as economic factors related to household wealth and technological development that affect the decision-making process. Improving the educational infrastructure, encouraging technological adoption and creating a more stable economic base for rural households could significantly contribute towards reducing the problem of child labor.
Keywords: 330; Labor and Human Capital; Kinderarbeit; Landwirtschaftlicher Familienbetrieb; Familienökonomik; Bildungsverhalten; Schätzung; Äthiopien